DSR: The Dynamic Source Routing Protocol for Multi-Hop Wireless Ad Hoc Networks - Johnson, David B.; Maltz, Dave; Broch, Josh (Ad Hoc Networking, 2001)
The Dynamic Source Routing protocol (DSR) is a simple and efficient routing protocol designed specifically for use in multi-hop wireless ad hoc networks of mobile nodes. DSR allows the network to be completely self-organizing and self-configuring, without the need for any existing network infrastructure or administration. The protocol is composed of the two mechanisms of Route Discovery and Route Maintenance, which work together to allow nodes to discover and maintain source routesto arbitrary destinationsin the ad hoc network. The use ofsource routing allows packetrouting to be trivially loop-free, avoidsthe need for up-to-date routing information in the intermediate nodes through which packets are forwarded, and allows nodes forwarding or overhearing packets to cache the routing information in them for their own future use. All aspects of the protocol operate entirely on-demand, allowing the routing packet overhead of DSR to scale automatically to only that needed to react to changesin the routes currently in use. We have evaluated the operation of DSR through detailed simulation on a variety of movement and communication patterns, and through implementation and significant experimentation in a physical outdoor ad hoc networking testbed we have constructed in Pittsburgh, and have demonstrated the excellent performance of the protocol. In this chapter, we describe the design of DSR and provide a summary of some of our simulation and testbed implementation results for the protocol.